2020
DOI: 10.1016/j.ocecoaman.2020.105321
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations and well-being: Gulf of Alaska fishing families in a changing landscape

Abstract: Over the last three decades, fishing families in the Gulf of Alaska have adapted to numerous multifaceted conditions in response to near constant flux in stocks, markets, governance regimes, and broader sociocultural and environmental changes. Based on an analysis of seven focus groups held across Gulf of Alaska fishing communities, this study explores the variety of strategies that families across the Gulf have employed to adapt to changing conditions from the 1980s to the present day. Furthermore, the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Within fisheries there is a vibrant body of literature documenting the multifaceted dimensions of well-being that people derive from fisheries, which are summarized in Table 2. Researchers have shown that fishing is associated with, amongst others, a connection to the water, family heritage, a sense of community, and identity (Hall-Arber et al, 2009;Holland et al, 2019;Szymkowiak, 2020a). Indeed fishing is often described as a way of life rather than an occupation by both fishers and their families, embedded with a sense of pride associated with their resilience (Britton, 2012;Szymkowiak, 2020a).…”
Section: Cumulative Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within fisheries there is a vibrant body of literature documenting the multifaceted dimensions of well-being that people derive from fisheries, which are summarized in Table 2. Researchers have shown that fishing is associated with, amongst others, a connection to the water, family heritage, a sense of community, and identity (Hall-Arber et al, 2009;Holland et al, 2019;Szymkowiak, 2020a). Indeed fishing is often described as a way of life rather than an occupation by both fishers and their families, embedded with a sense of pride associated with their resilience (Britton, 2012;Szymkowiak, 2020a).…”
Section: Cumulative Effectsmentioning
confidence: 99%
“…Researchers have shown that fishing is associated with, amongst others, a connection to the water, family heritage, a sense of community, and identity (Hall-Arber et al, 2009;Holland et al, 2019;Szymkowiak, 2020a). Indeed fishing is often described as a way of life rather than an occupation by both fishers and their families, embedded with a sense of pride associated with their resilience (Britton, 2012;Szymkowiak, 2020a). Despite evidence of the diversity of well-being that people derive from fisheries, ecosystem assessments have largely focused on economic benefits, or at most a highly condensed subset of well-being components including equity measured with respect to gear conflicts, livelihood measured with respect to employment and revenues, family connection and physical safety measured with respect to time at sea (Fulton et al, 2014(Fulton et al, , 2018DePiper et al, 2017;Zador et al, 2017;Gaichas et al, 2018;Okamoto et al, 2020).…”
Section: Cumulative Effectsmentioning
confidence: 99%
See 3 more Smart Citations